Making Use of the Land: The Political Ecology of China's First Empire. Issue 1 (January 2023) - Lander, Brian
Abstract: This article uses a case study of the Qin Empire to explore the ecology of an agrarian political system, analysis that has become possible because of the archaeological excavation of Qin administrative documents. Qin's power derived from photosynthesis, and its empire mobilized this energy and used it to conquer territory and expand its productivity. The state's power was based on its ability to extract taxes in grain from its subjects, store it in granaries, and then use it to feed laborers working on state projects. Grain and most other taxable materials were too bulky to move very far, so the government relied on a subcontinent-wide system of information gathering and processing that allowed officials at the capital to make decisions about local resource use. Qin's centralized bureaucratic system became the standard model of political organization in China, so it offers clues into the effects subsequent empires would have on their environments.